Pengaruh Power Dinamika Oseanografi Terhadap Perubahan Morfologi Muara Sungai Air Rami dan Selagan Jaya, Provinsi Bengkulu. (The Influence of Oceanographic Power Dynamics on Morphological Changes of Air Rami and Selagan Jaya Estuary, Bengkulu Province) - Supiyati; Suwarsono; Septi Johan; Dea Apriliani; Elmiati (Asosiasi Peneliti dan Teknisi Kehutanan dan Lingkungan Hidup Indonesia (APTKLHI), 2024)
Bengkulu Province has many river estuaries that experience rapid morphological change, making it a watershed problem because it can trigger sedimentation downstream. This research determined the characteristics and influence of oceanographic power dynamics on morphological changes of river estuaries in Bengkulu. The methods are in situ measurements of oceanographic dynamics parameters, visual aerial photography from drones, and maps of the Air Rami and Selagan Jaya Estuary from USGS Landsat-8 satellite imagery. Based on the study's results, the characteristics of the study area have a mixed tidal type leaning to double daily with a formzhal value of 0.509 in the Air Rami and 0.491 in Selagan Jaya. Morphological changes in the estuary are caused by sedimentation, which is influenced by the interaction of oceanographic power dynamics in the form of tides, waves, currents from the watershed, tidal currents, longshore currents, and sediment. This condition is due to the weakening of the current at the mouth of the estuary due to the confluence of tidal currents, currents from upstream of the watershed, and longshore currents so that sediment transport caused by longshore currents is retained and accumulates at the mouth of the estuary. At high tide, the current enters the estuary carrying sediment that has accumulated at the mouth of the estuary. At low tide, when the current speed is slower, it cannot bring the sediment back, so it settles in the estuary. In addition, the inflow of sediment from the upstream watershed into the estuary also contributes to the increasing sedimentation.